Makna Simbolik Pantun dalam Tradisi Lisan Hempang Pintu dan Makan Beradab pada Pernikahan Melayu Langkat - Nurmala Sari; Prima Nucifera; Tanita Liasna (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2026)
Pantun occupies a central position in the Langkat Malay wedding tradition as a medium for transmitting cultural values, social norms, and collective identity; however, the symbolic meanings embedded in the Hempang Pintu and Makan Beradab oral traditions have not been comprehensively examined through Peircean semiotics. This study investigates how icons, indices, and symbols are constructed in pantuns performed during these traditions and explores the cultural meanings they convey. Employing a descriptive qualitative approach, the research analyzed 85 pantun stanzas from four traditional wedding processions using Charles Sanders Peirce's triadic semiotic model, supported by observation, note-taking, and in-depth interviews. The findings identified 20 icons, 28 indices, and 76 symbols, indicating that symbolic signs dominate because pantuns predominantly communicate figurative meanings and culturally shared conventions. The symbolic meanings encompass religiosity, Malay cultural identity, respect for customary traditions, protection of the bride's dignity, and moral guidance for married life. The study contributes a novel systematic mapping of the distribution of icons, indices, and symbols across the four Hempang Pintu and Makan Beradab processions in Hinai District and demonstrates that pantun functions as a dynamic system of cultural communication that plays a vital role in preserving Malay cultural heritage amid ongoing modernization.